The Dubousset Functional Test is a Novel Assessment of Physical Function and Balance. Issue 10 (October 2019) - Diebo, Bassel G.; Challier, Vincent; Shah, Neil V.; Kim, David; Murray, Daniel P.; Kelly, John J.; Lafage, Renaud; Paulino, Carl B.; Passias, Peter G.; Schwab, Frank J.; Lafage, Virginie
Abstract: Background: Currently, the functional status of patients undergoing spine surgery is assessed with quality-of-life questionnaires, and a more objective and quantifiable assessment method is lacking. Dr. Jean Dubousset conceptually proposed a four-component functional test, but to our knowledge, reference values derived from asymptomatic individuals have not yet been reported, and these are needed to assess the test's clinical utility in patients with spinal deformities. Questions/purposes: (1) What are the reference values for the Dubousset Functional Test (DFT) in asymptomatic people? (2) Is there a correlation between demographic variables such as age and BMI and performance of the DFT among asymptomatic people? Methods: This single-institution prospective study was performed from January 1, 2018 to May 31, 2018. Asymptomatic volunteers were recruited from our college of medicine and hospital staff to participate in the DFT. Included participants did not report any musculoskeletal problems or trauma within 5 years. Additionally, they did not report any history of lower limb fracture, THA, TKA, or patellofemoral arthroplasty. Patients were also excluded if they reported any active medical comorbidities. Demographic data collected included age, sex, BMI, and self-reported race. Sixty-five asymptomatic volunteers were included in this study. Their mean age was 42 ± 15 years; 27 of the 65 participants (42%) were women. Their mean BMI was 26 ± 5 kg/m 2 . The racial distribution of the participants was 34% white (22 of 65 participants), 25% black (16 of 65 participants), 15% Asian (10 of 65 participants), 9% subcontinental Indian (six of 65 participants), 6% Latino (four of 65 participants), and 10% other (seven of 65 participants). In a controlled setting, participants completed the DFT after verbal instruction and demonstration of each test, and all participants were video recorded. The four test components included the Up and Walking Test (unassisted sit-to-stand from a chair, walk forward/backward 5 meters [no turn], then unassisted stand-to-sit), Steps Test (ascend three steps, turn, descend three steps), Down and Sitting Test (stand-to-ground, followed by ground-to-stand, with assistance as needed), and Dual-Tasking Test (walk 5 meters forwards and back while counting down from 50 by 2). Tests were timed, and data were collected from video recordings to ensure consistency. Reference values for the DFT were determined via a descriptive analysis, and we calculated the mean, SD, 95% CI, median, and range of time taken to complete each test component, with univariate comparisons between men and women for each component. Linear correlations between age and BMI and test components were studied, and the frequency of verbal and physical pausing and adverse events was noted. Results: The Up and Walking Test was completed in a mean of 15 seconds (95% CI, 14-16), the Steps Test was completed in 6.3 seconds (95% CI, 6.0-6.6), the Down and Sitting Test was completed in 6.0 seconds (95% CI, 5.4-6.6), and the Dual-Tasking Test was performed in 13 seconds (95% CI, 12-14). The length of time it took to complete the Down and Sitting (r = 0.529; p = 0.001), Up and Walking (r = 0.429; p = 0.001), and Steps (r = 0.356; p = 0.014) components increased with as the volunteer's age increased. No correlation was found between age and the time taken to complete the Dual-Tasking Test (r = 0.134; p = 0.289). Similarly, the length of time it took to complete the Down and Sitting (r = 0.372; p = 0.005), Up and Walking (r = 0.289; p = 0.032), and Steps (r = 0.366; p = 0.013) components increased with increasing BMI; no correlation was found between the Dual-Tasking Test's time and BMI (r = 0.078; p = 0.539). Conclusions: We found that the DFT could be completed by asymptomatic volunteers in approximately 1 minute, although it took longer for older patients and patients with higher BMI. Clinical Relevance: We believe, but did not show, that the DFT might be useful in assessing patients with spinal deformities. The normal values we calculated should be compared in future studies with those of patients before and after undergoing spine surgery to determine whether this test has practical clinical utility. The DFT provides objective metrics to assess function and balance that are easy to obtain, and the test requires no special equipment.